Does vitamin E play a role in the primary prevention of stroke? - Hidayat, Adi (Faculty of Medicine, Trisakti University, 2011)
A few decades ago it was generally accepted from experimental studies, animal experiments, and epidemiological cohort studies that atherogenesis is linked to oxidative stress and that antioxidant supplementation, notably vitamin E supplementation, is associated with a low incidence of cardiovascular disease (CVD). This view led to the widespread use of vitamin E and other antioxidants for reducing CVD morbidity and mortality. In vitro and animal studies on antioxidant and anti-inflammatory properties of alpha- and gamma-tocopherols also found that these antioxidants had anti-inflammatory properties.